Blockchain Techniques for Secure Storage of Data in Cloud Environment - et. al., Praveen Kumar Kollu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The need for Blockchain advancement, as well as the importance of its use, has fueled ongoing research in a variety of theoretical and practical fields. Even as it is still in its early stages of development, the blockchain is being seen as a forward-thinking approach to modern technology issues such as decentralization, identification, confidence, character, data ownership, and information-driven decisions. The blockchain breakthrough offers major feedback when effectively searching for the optimal solution to storing and accessing cloud data. This essay examines the use of blockchain technologies to secure cloud computing. This research paper also presents a framework for secure storage of data in cloud computing environment. This framework makes use of smart contracts and access list for ensuring data security.